Role and Performance of Agricultural Sector from 1969 to 2007 (Journal of Basic and Applied Sciences, 2016)
This paper aims to summarize the reality of the Libyan agricultural sector from 1969 to 2007 by showing the development of agricultural production, performance of the agricultural sector, challenges, problems and constraints of agriculture in Libya. Agriculture and livestock have been important components of the Libyan social, political and economic fabric, with more than half the population engaged in agriculture in some form until the 1950s and 1960s. The sector has received generous subsidies in the quest for self-sufficiency. However, The Libyan agricultural growth has been inversely related with growth in the Libyan oil sector. Also, the agricultural sector’s contribution to gross domestic product (GDP) has been declining since the discovery of oil in 1958. According to the Ministry of Agriculture (MoA, 2008) food imports have rapidly increased over recent decades, reaching approximately $ 270 million in 2007. Cereals contribute the largest share of these imports with 35%; wheat alone representing 6% of total imports in 2007. Apart from limited wheat and barley production, the major agricultural production consists of mostly fruit and vegetables especially, dates, grapes, olives, citrus, watermelon, onions, tomatoes and potatoes. In short, the agricultural sector still faces many challenges, problems and constraints including limited agricultural resources, and the ability to exploit these resources efficiently. Also, unfortunately, performance of agriculture in Libya has not been up to expectations and has been characterized over the decades by ups and downs.
Keywords: Libya; Agricultural sector; GDP; Food imports; Self-sufficiency